1992
DOI: 10.1021/j100202a052
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling of partially diffusion-controlled reactions in spur kinetics

Abstract: Stochastic simulation techniques have been developed for modeling partially diffusion-controlled reactions in spur kinetics. These methods have been used to examine whether deviation from full diffusion control influences the overall spur chemistry.Studies of idealized two-species spurs suggest that the time dependence of the kinetics is not affected by the nature of the reaction; however, the overall chemistry of a spur can be influenced by a deviation from full diffusion control as whether the reaction is fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…A value of 0.5 nm was chosen for a, then the reaction velocity v was estimated by [33] (33) k D a a D = ′ + ′ In IRT simulation, for the realization of a system of n p particles, it is necessary to consider n p (n p -1)/2 reaction times by Eq. (36). When modeling scavenger reactions, it is also necessary to include n s OH scavenger particles, and consider the reaction OH + scavenger → removal of OH (38) The total number of the combination was too large to handle even at dilute scavenger concentrations, so we treated the scavenger as a continuum, then each radical was initially surrounded by a homogeneous distribution of scavengers.…”
Section: Independent Reaction Times (Irt) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A value of 0.5 nm was chosen for a, then the reaction velocity v was estimated by [33] (33) k D a a D = ′ + ′ In IRT simulation, for the realization of a system of n p particles, it is necessary to consider n p (n p -1)/2 reaction times by Eq. (36). When modeling scavenger reactions, it is also necessary to include n s OH scavenger particles, and consider the reaction OH + scavenger → removal of OH (38) The total number of the combination was too large to handle even at dilute scavenger concentrations, so we treated the scavenger as a continuum, then each radical was initially surrounded by a homogeneous distribution of scavengers.…”
Section: Independent Reaction Times (Irt) Methodsmentioning
confidence: 99%
“…The random reaction time T r was determined by solving Eq. (25) as (36) where ξ is a random number uniformly distributed between 0 and 1 and erfc -1 (x′) = x is the inverse of erfc (x) = x′ [33]. The probability of the reaction is largest when T r is the smallest.…”
Section: Decay Channels Of Water Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…55 Nevertheless, it has been shown that the yields calculated with SBS are equivalent to IRT when using two-particle systems. 3,24,56 In addition, the G-values calculated with the SBS approach depended to some extent on the minimum time step which is implemented in a dynamic time partition. 19 To quantify this effect, we calculated G-values for • OH produced by 1 MeV electrons using a fixed minimum time step to 0.1 ps.…”
Section: Discussionmentioning
confidence: 99%
“…The differences might be attributed in part to the independent pair approximation taken by the IRT approach whereas the SBS considers a multiparticle system 55 . Nevertheless, it has been shown that the yields calculated with SBS are equivalent to IRT when using two‐particle systems 3,24,56 . In addition, the G‐values calculated with the SBS approach depended to some extent on the minimum time step which is implemented in a dynamic time partition 19 .…”
Section: Discussionmentioning
confidence: 99%